2013
DOI: 10.1136/neurintsurg-2013-010737
|View full text |Cite
|
Sign up to set email alerts
|

Temporary Solitaire stent neck remodeling in the coiling of ruptured aneurysms

Abstract: Stent retrieval and removal can be done safely in selected cases at the end of stent-assisted coil embolization using the Solitaire AB device. This technique avoids the need for continuing antiplatelet therapy, which can be particularly important in the setting of acute subarachnoid hemorrhage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…Since the publication of our article, 2 we have treated 10 aneurysms in 8 patients by using this technique, raising our experience to 13 procedures. This technique was used for the treatment of wide-neck aneurysms of the anterior communicating artery (n ϭ 4), internal carotid artery termination (n ϭ 2), basilar artery tip (n ϭ 2), middle cerebral artery bifurcation (n ϭ 1), or the posterior communicating artery (n ϭ 1).…”
mentioning
confidence: 99%
“…Since the publication of our article, 2 we have treated 10 aneurysms in 8 patients by using this technique, raising our experience to 13 procedures. This technique was used for the treatment of wide-neck aneurysms of the anterior communicating artery (n ϭ 4), internal carotid artery termination (n ϭ 2), basilar artery tip (n ϭ 2), middle cerebral artery bifurcation (n ϭ 1), or the posterior communicating artery (n ϭ 1).…”
mentioning
confidence: 99%
“…7 The technique of temporary stent-assisted neck remodeling has been reported with the Enterprise stent 8 and recently with the Solitaire AB stent. 9 Contrary to a series by Almekhlafi et al, 9 we did not use antiplatelet therapy; thus theoretically reducing the risk of hemorrhagic complications linked to intraprocedural rupture of the aneurysm and to subsequent surgical interventions to treat intracranial hypertension such as EVD placement or decompressive craniectomy. 16 In our series, 4 of the 8 patients underwent emergent EVD placement, and no hemorrhagic complication was noted.…”
Section: Discussionmentioning
confidence: 92%
“…9 However, all patients received aspirin before the procedure, and 1 of 3 patients required antiplatelet therapy after the intervention. 9 The aim of this study was to investigate the feasibility, safety, and efficacy of the use of temporary Solitaire AB SAC for the treatment of acutely ruptured wide-neck aneurysms without perioperative antiplatelet therapy.…”
mentioning
confidence: 99%
“…All patients had a history of spontaneous subarachnoid hemorrhage (SAH). The study inclusion criteria were as follows: i) History of SAH confirmed by a head computed tomography examination, which showed the hemorrhage from the aneurysms; ii) very small aneurysms with a size of ≤3 mm in diameter diagnosed by digital subtraction angiography (DSA); iii) no other aneurysms in the brain; and iv) aneurysms meeting the indication for Solitaire AB stent-assisted coiling embolization (4)(5)(6). Exclusion criteria were as follows: i) No history of SAH; ii) intracranial hemorrhage not associated with the aneurysms; iii) intracranial hematoma with a volume of ≥30 ml; and iv) parent arteries that were tortuous or exhibited severe stenosis, which indicated that Solitaire AB stent-assisted coiling embolization was not suitable.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies have demonstrated that Solitaire AB stent-assisted coiling embolization is a safe and effective treatment for wide-necked or complex intracranial aneurysms (3)(4)(5)(6). In addition, Zhao et al reported that Solitaire AB stents are effective for the treatment of very small (≤3 mm) and small (3-10 mm) ruptured and unruptured intracranial aneurysms (7).…”
Section: Introductionmentioning
confidence: 99%